Spatial Distribution and Predictive Significance of Dendritic Cells and Macrophages in Esophageal Cancer Treated With Combined Chemoradiotherapy and PD-1 Blockade - Ma, Xiaoxue; Guo, Zhoubo; Wei, Xiaoying; Zhao, Gang; Han, Dong; Zhang, Tian; Chen, Xi; Cao, Fuliang; Dong, Jie; Zhao, Lujun; Yuan, Zhiyong; Wang, Ping; et al. (Frontiers in Immunology, 2022)
Background The first clinical study (NCT03671265) of first-line chemoradiotherapy combined with PD-1 blockade showed promising treatment outcomes in locally advanced esophageal squamous cell carcinoma (ESCC). However, partial patients did not respond to the combination treatment. The roles of dendritic cells (DCs) and macrophages in this combination treatment remain poorly understood. Methods We performed multiplexed immunofluorescence method to identify CD11c+ DCs, CD68+ macrophages, and their PD-L1- or PD-L1+ subpopulations in paired tumor biopsies (n = 36) collected at baseline and during the combination treatment (after radiation, 40 Gy) from the phase Ib trial (NCT03671265). We applied whole exome sequencing in the baseline tumor biopsies (n = 14) to estimate tumor mutation burden (TMB). We dynamically investigated the spatial distribution of DCs and macrophages under chemoradiotherapy combined with PD-1 blockade, and evaluated the association between their spatial distribution and combination outcome, and TMB. Results The results showed that high percentages of PD-L1- DCs and macrophages in the baseline tumor compartment, but not in the stromal compartment, predicted improved OS and PFS. Chemoradiotherapy combined with PD-1 blockade promoted DCs and macrophages to migrate closer to tumor cells. During combination treatment, PD-L1- tumor cells were nearest to PD-L1- DCs and macrophages, while PD-L1+ tumor cells were next to PD-L1+ DCs and macrophages. High TMB was closely associated with a shorter distance from tumor cells to DCs and macrophages. Shorter distance between PD-L1+ tumor cells and PD-L1+ DCs or PD-L1- macrophages during the combination was correlated with better OS. Shorter distance between PD-L1- tumor cells and PD-L1- macrophages during combination was associated with both longer OS and PFS. Conclusions PD-L1- or PD-L1+ DCs and macrophages exhibit distinct spatial distribution in ESCC. The close distance between tumor cells and these antigen-presenting cells (APCs) is critical to the clinical outcome in chemoradiotherapy combined with PD-1 blockade in ESCC patients. Our results highlight the predictive potential of spatial patterns of APCs in chemoradiotherapy combined with immunotherapy and reveal the underlying mechanism of APCs participating in chemoradiotherapy-induced antitumor immune response in ESCC.